Performance of social integration programs for immigrants and influential factors: Evidence from the Korea Immigration and Integration Program (KIIP). (March 2021) - Lim, Dong-Jin
Abstract: The purpose of this study is to analyze by immigrants' characteristics their participation in and social integration performance on the Korea Immigration and Integration Program (KIIP), which the Korean government provides for education in Korean language and basic knowledge about Korea to support the social integration of immigrants; on that basis, it suggests policy implications. For this purpose, I surveyed 1, 014 immigrants, including 800 participants and 214 non-participants of the KIIP; among these individuals, 46.1 % had experienced discrimination. There were several reasons they felt they had been discriminated against; general prejudice against immigrants in South Korea and lack of Korean language ability were the most common. The immigrants who participated in KIIP included several groups: visiting relatives, those who had moved to be with their families, immigrants living in Seoul, Vietnamese people, non-Korean spouses, longer-term non-Korean residents, and non-Han Chinese individuals. Those immigrants who participated in KIIP showed a high degree of adaptability to Korean culture. Korean language proficiency, a key output of KIIP, was the most important factor in improving immigrants' cultural adaptation, sense of societal belonging, and economic conditions.